Cooking the books: The case of Malaysian Listed Companies - Abdul Hamid, Fathilatul Zakimi (Center for Promoting Ideas (CPI), USA, 2013)
Cooking the books refers to fraudulent accounting activities undertaken by a business to falsify its financial statements. Thus, the objectives of this study are to investigate what the cooking-the-books activities carried out by businesses consist of, how they conduct them, and what the impact is on the business and its shareholders.The case study sample companies are two Malaysian companies that had received various awards from reputable third-party organizations. On the other hand, the activities undertaken in both companies have caused them to be labelled as Malaysian mini Enrons. We employ a qualitative research methodology as most prior research employs a quantitative methodology to investigate the determinant factors in businesses’ cooking-the-book activities.The result of the study shows that the managers have used their positions, prior experience, and regulatory loopholes in their activities.Furthermore, the financial report restatement and higher reported earnings are the early warning s ignals of their activities.As a result of this, the Malaysian Securities Commission has revised the corporate governance code, and among others incorporated the Audit Oversight Board, known in the US as the Public Company Accounting Oversight Board.